2015
DOI: 10.1037/adb0000069
|View full text |Cite
|
Sign up to set email alerts
|

The influence of impulsiveness on binge eating and problem gambling: A prospective study of gender differences in Canadian adults.

Abstract: This study investigated the degree to which facets of impulsiveness predicted future binge eating and problem gambling, 2 theorized forms of behavioral addiction. Participants were 596 women and 406 men from 4 age cohorts randomly recruited from a Canadian province. Participants completed self-report measures of 3 facets of impulsiveness (negative urgency, sensation seeking, lack of persistence), binge-eating frequency, and problem-gambling symptoms. Impulsiveness was assessed at baseline, and assessments of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Urgency is one of the facets of impulsivity that has received increasing empirical attention given its hypothesized association in the etiology and maintenance of addictions. Negative urgency, in particular, has been robustly associated with substance use disorders such as alcohol ( 82 ) as well as behavioral addictions such as gambling ( 83 ), video games ( 84 ), compulsive buying ( 85 ), binge eating ( 86 ), and sex ( 87 ).…”
Section: Negative Urgencymentioning
confidence: 99%
See 1 more Smart Citation
“…Urgency is one of the facets of impulsivity that has received increasing empirical attention given its hypothesized association in the etiology and maintenance of addictions. Negative urgency, in particular, has been robustly associated with substance use disorders such as alcohol ( 82 ) as well as behavioral addictions such as gambling ( 83 ), video games ( 84 ), compulsive buying ( 85 ), binge eating ( 86 ), and sex ( 87 ).…”
Section: Negative Urgencymentioning
confidence: 99%
“…The association between negative urgency has also been documented in longitudinal studies with behavioral addictions. In a large sample of Canadian adults ( N = 1,002), Farstad et al ( 86 ) found that negative urgency was the only facet of impulsivity that predicted problematic gambling and binge eating, suggesting negative urgency may be an important transdiagnostic mechanism in the expression of both gambling disorder and binge eating disorder, and a component of impulsivity that needs to be addressed in treatment. Indeed, negative urgency has been related to poorer treatment outcomes including relapse in substance use disorder ( 88 ).…”
Section: Negative Urgencymentioning
confidence: 99%
“…Case-control studies also reveal elevations in urgency in a diverse range of diagnostic groups, including individuals diagnosed with bipolar I disorder [12], eating disorders [13], major depressive disorder [14], and schizophrenia [15]. Finally, urgency prospectively predicts a range of symptoms and risky behaviors, such as depression, self-injury, and substance use outcomes [1620]. Together, these findings support the premise that tendencies to react impulsively to emotion states are transdiagnostic [21].…”
Section: Introductionmentioning
confidence: 99%
“…Providing support for this supposition, impulsivity is a key characteristic of symptoms of bulimia nervosa, binge‐eating disorder (Waxman, ), and gambling disorder (Blaszczynski & Nower, ; Hodgins & Holub, ; Tavares & Gentil, ). Indeed, impulsivity, particularly negative urgency, has been suggested to independently contribute to the expression of both binge‐eating and gambling disorders in cross‐sectional (Fischer & Smith, ) as well as longitudinal samples (Farstad et al, ). Moreover, people with bulimia nervosa/binge‐eating disorder and comorbid gambling disorder report greater levels of impulsivity (Jiménez‐Murcia et al, ), suggesting that impulsivity may represent a shared risk for both disorders.…”
Section: Introductionmentioning
confidence: 99%